Development Of Eight Shaped Systems For Slope Stabilization - Safari, Aboulfazl (2012)
Slope stability has been an important topic in the field of geotechnical engineering. The varieties of techniques were investigated to provide a stable condition for slopes by improving engineering properties of soils. Utilizing recycled materials is one the favourable methods for soil stabilization that covers all environmental and technical aspects. Recycled tyre has been widely used for this purpose due to the excellent physical and mechanical properties such as light weight, high durability, high tensile strength, and very low cost. Round shaped of recycled tyre has been reported to be generally used as slope stability elements.